Multi-stage bioengineering of a layered oesophagus with in vitro expanded muscle and epithelial adult progenitors - Luca Urbani (Nature Portfolio, 2018)
Combining decellularised scaffolds with patient-derived cells holds promise for bioengineering of functional tissues. Here the authors develop a two-stage approach to engineer an oesophageal graft that retains the structural organisation of native oesophagus.